Pusat Rehabilitasi Tunadaksa di Denpasar - Pradnyasuari, Cokorda Istri Krisna Sukma; ., Widiastuti; Swanendri, Ni Made (Jurnal Arsitektur Universitas Udayana; Vol 9 No 02 (2021): Jurnal Arsitektur, Universitas UdayanaDO - 10.24843/jaunud.v9i02.66209, 2021)
Tunadaksa  (physical disabilities) is a disability that results in impaired body functions caused by several things such as accident tragedy, malnutrition, lack of living facilities, and inability to maintain health. The increase in the number of tunadaksa requires the Bali Province to have facilities that can accommodate, treat, and repair damaged organs by designing a rehabilitation center. The available facilities and infrastructure are expected to provide comfort for patients, visitors, and medical personnel. Patients with disabilities, especially disabled people, have the right to equal opportunities in terms of services to make it easier for patients to carry out activities. The specialty of tunadaksa or people with disabilities requires designers to design a room with a high level of comfort to facilitate the users of assistive devices in carrying out activities. The comfort is created from the elements that make up space itself, thus it can affect the psychology of the community on it. This forming element is in the form of calculating the amount of circulation and selecting the characteristics of the material used to make it easier for the users of assistive devices to maneuver in the lobby. Keywords: Rehabilitation, Tunadaksa, Comfort, Circulation